LAND AND SEA: CARL SCHMITT’S PHILOSOPHICAL GEOGRAPHY - Giorgi Tavadze (European Scientific Journal, ESJ, 2013)
The present article discusses Carl Schmitt’s philosophical geography according to his work Land and Sea. A World-historical reflection. In Schmitt’s philosophical geography we can identify five major areas: 1. Land and sea as antagonistic elements; 2. Spatial revolution and its consequences; 3. The world-historical tension between Catholicism and Protestantism against the background of the antagonism between the land and the sea; 4. Industrial Revolution and social-technical progress as the foundational factors of new elemental forces; 5. In a given world-historical situation, a man has the possibility to make a choice between the elements and therefore transcend any former spatial limits whilst gaining new spatial consciousness and horizons. This examination also traces the possible influence of Ernst Kapp and Friedrich Ratzel on Schmitt’s views. At the end Schmitt’s contribution is discussed in relation to global changes occurring in contemporary world.